DISTRIBUSI DAN PENANGANAN PASCAPANEN KACANG PANJANG (Vigna sinensis L.) DARI KECAMATAN BATURITI KE KOTA DENPASAR - Ary Gunada, A A Gede; Wrasiati, Luh Putu; Anom Yuarini, Dewa Ayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 2 (2015): Juni)
The aims of this study were 1) to find out the distribution line of long beans (Vigna sinensis L.) that produced in Baturiti to Denpasar, 2) to find out post-harvest handling in each distribution line that is passed and post-harvest handling that has been done, 3) to determine the marketing and profit margin of each distribution from Baturiti to Denpasar. This study was using survey method. This study showed that there were 6 distribution line of long beans from Baturiti to Denpasar and all lines had experienced in sorting and grading on the collectors and traders. The highest marketing margin was Rp 8.000/kg and the highest profit margin was Rp. 6.805/kg which were found in line 4 (farmer-collector-seller-retailer-customer). Meanwhile the lowest marketing margin was Rp.4.250/kg and the lowest profit margin was Rp.3.685/kg which were found in line 1 (farmer-seller-customer)
Keywords: 44,